The Influence of Competitive Advantage, Market Orientation, and Partnerships on Reddoorz's Marketing Performance - Neno, Yohanes Robinsius; Miswanto, Miswanto; Siregar, Baldric; Biyanto, Frasto (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
The aim of this study is to evaluate the impact of competitive advantage, market orientation, and partnerships on the marketing performance of RedDoorz, a rapidly growing budget accommodation platform in Indonesia. Using a quantitative approach, primary data were collected through questionnaires distributed to 40 selected respondents using a purposive sampling technique. Based on multiple linear regression analysis, the findings indicate that competitive advantage and partnerships have a positive and significant influence on marketing performance, while market orientation does not show a significant effect. Theoretically, this study supports the resource-based view theory and serves as a reference for future research in this area. Practically, the findings can be utilized by RedDoorz management to formulate strategies aimed at enhancing competitiveness and marketing performance amidst increasingly intense competition.